Edward I. Bullock & William Johnson, The General Statutes of the Commonwealth of Kentucky 669 (1873) - (:unkn) unknown (My University, 1873)
Ch. 76, art. V,§ 3: A soldier who unnecessarily, or without order from a superior officer, comes to any parade with his musket, rifle, or pistol loaded with ball, slug, or shot, or shall so load the same while on duty, or unnecessarily, or without order from a superior officer, discharges the same when going to, returning from, or upon parade, shall forfeit not less than one nor more than five dollars.
Keywords: ARMED FORCES